An analysis of the throwing technique of college male javelin throwers in a competition - Makino, M.; Hatakeyama, S.; Ae, M. (ISBS Proceedings Archive (Michigan), 2020)
The purposes of this study were to investigate the throwing technique for Japanese college male athletes in official competitions, focusing on the torso and throwing arm motions, and to obtain basic information for the improvement in their techniques. Twenty-four male college throwers were videotaped and analysed for their throwing motion using the three-dimensional DLT method and caluclated the joint angle. The throwers were divided into three groups based on their records. Comparison to the ELITE throwers, the timing of the torso rotation for college groups was delayed. Significant differences in the right shoulder horizontal abduction angle around the left foot touchdown among the three groups were found. These results imply that the right shoulder horizontal abduction may be one of the factor determining throwing distance as well as early torso rotation. The discussion suggested that the concept change from the late rotation to the early rotation of the torso for the college male javelin throwers would result in a large horizontal abduction and a quick horizontal adduction of right shoulder.